Effect of DGAT1 polymorphisms on the estimated breeding values of Czech Simmental sires - L. Hanusová; A. Míková; L. Večerek; D. Schroeffelová; V. Řehout; L. Tothová; K. Vernerová; B. Hosnedlová; J. Čítek (Czech Journal of Animal Science, 2014)
The aim was to evaluate the effect of polymorphisms in the promoter and in the coding region of the DGAT1 gene on the estimated breeding values (EBV) of Czech Simmental sires. The K232A polymorphism (n = 191) in the coding region was genotyped by PCR/RFLP, and the KU and SA polymorphisms in the promoter (n = 203) were identified in an automatic sequencer. In the K232A polymorphism, the frequency of the genotype AA (Alanine) was greater than that of the genotype KA, the homozygous genotype KK (Lysine) was not found. Similarly, the allele A predominated over the K allele (0.945 and 0.055). The EBV for milk performance have been assigned to the genotypes, and the associations quantified. For the AA genotype and A allele, positive association with EBV of milk yield and protein yield was found, and negative association with the breeding values of fat percentage and yield, and protein percentage, but only the value of fat content was found to be significant. The positive non-significant association of the A variant with the protein yield was caused by the high milk yield. In the KU polymorphism, the CC genotype was associated significantly with lower EBV for the fat percentage, both the C allele and the CC genotype were associated with higher EBV for milk yield, so both the fat and the protein yield were non-significantly increased. For the diplotypes K232A/KU, there was a significant association with the fat percentage. The AACC combination seemed to have some breeding potential. The K232A polymorphism explained maximum of 6.2% of EBV variability, the KU polymorphism of 4.4%, and the SA polymorphism of 4.2%. The diplotypes K232A/KU explained maximum of 7.4% of variability. The highest proportion of variability was explained for fat percentage. The results confirmed the important role of the BTA14 region in controlling milk performance.